Current Fertility Status Does Not Predict Sociosexual Attitudes and Desires in Normally Ovulating Women. (7th January 2021) - Thomas, Andrew G.; Armstrong, Stephanie L.; Stewart-Williams, Steve; Jones, Benedict C.
Previous research has found that women at peak fertility show greater interest in extra-pair sex. However, recent replications have failed to detect this effect. In this study, we add to this ongoing debate by testing whether sociosexuality (the willingness to have sex in the absence of commitment) is higher in women who are at peak fertility. A sample of normally ovulating women ( N = 773) completed a measure of sociosexuality and had their current fertility status estimated using the backward counting method. Contrary to our hypothesis, current fertility was unrelated to sociosexual attitudes and desires, even when relationship status was included as a moderator. These findings raise further doubts about the association between fertility and desire for extra-pair sex.